A novel computational framework for the analysis of bistable composite beam structures. (1st February 2021) - De Pietro, G.; Giunta, G.; Hui, Y.; Belouettar, S.; Hu, H.; Carrera, E.
Abstract: Over the last few years, several studies have shown the potential of multi-stability in engineering applications such as shape-adaptive structures and energy harvesting devices. Due to their highly non-linear mechanics, multi-stable structures are inherently more complex to model than conventional engineering structures. Especially when composite materials are involved, two-dimensional or three-dimensional finite elements solutions are often required in order to have a thorough understanding of the stress field evolution within the structure throughout the snap-through phenomenon. Nevertheless, such modelling strategies yield time-consuming design and optimisation procedures. In order to exploit multi-stability in industrial applications, an enhancement of the existing modelling capabilities is needed. Starting from the state-of-the-art methodologies available in the literature, a novel computational framework is proposed in this study for the analysis of bistable composite beam structures. An advanced structural modelling approach based on Carrera's Unified Formulation (CUF) is adopted. By harnessing the potential of CUF, a full in-plane stress field (including axial, transverse shear and transverse normal stress) can be accurately yet efficiently predicted with no need to resort to two-dimensional or three-dimensional FEM solutions. Furthermore, the equilibrium paths of slender as well as thicker bistable beams are investigated, showing that refined predictions of the stable geometries and snap-through loads in bistability analyses can be obtained via the proposed advanced one-dimensional formulation. Validation of the proposed modelling approach towards reference solutions and commercial software finite elements is provided.